2020
DOI: 10.1088/2053-1591/ab70dd
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of cobalt oxide nanoparticles for potential biological applications

Abstract: Cobalt oxide nanoparticles (Co 3 O 4 -Nps) have many applications and now a days the green methods of synthesis of these NPs are preferred over other methods because of associated benefits. In this study, Co 3 O 4 -Nps were synthesized by using leaves extract of Populus ciliata (safaida) and cobalt nitrate hexa hydrate as a source of cobalt. The synthesized NPs were analyzed by different techniques such as fourier transform spectroscopy (FTIR), x-ray diffraction (XRD), transmission electron microscopy (TEM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(58 citation statements)
references
References 23 publications
2
56
0
Order By: Relevance
“…Furthermore, smaller particles were amalgamated to form clusters of larger size. Other researchers made similar observations about the Co NPs [ 26 27 ]. In general, the particle shape and size were uniform with a smooth surface, which could be related to contact with the bacteria to demonstrate increased antibacterial activities [ 27 28 ].…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Furthermore, smaller particles were amalgamated to form clusters of larger size. Other researchers made similar observations about the Co NPs [ 26 27 ]. In general, the particle shape and size were uniform with a smooth surface, which could be related to contact with the bacteria to demonstrate increased antibacterial activities [ 27 28 ].…”
Section: Resultssupporting
confidence: 67%
“…The Co NPs played a role as a potential antiseptic to control the infections by other bacteria such as B. Subtilis and Pseudomonas Sp . [ 10 27 ]. It was also suggested that Co NPs were biosafe when cell cytotoxicity tests produced minimal damage to human cells at a nanoparticle concentration of 100 μg/ml [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proved that the NPs with smaller size, exhibit enhanced antimicrobial potential due to their direct interaction with microbial membranes ( Rydz et al, 2019 , Kasemets et al, 2019 ). Moreover, green synthesis using plant extracts results in capping of phytochemicals on the NPs surface that can be an important factor in defining antioxidant and enzyme inhibition activity of the synthesized Co 3 O 4 -NPs and MgO-NPs ( Hafeez et al, 2020 , Abinaya et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…XRD technique was also utilized to study the arrangement of green synthesized Co 3 O 4 ( Figure 8 ). Well-defined peaks were not observed in diffraction patterns, which suggests that the obtained nanoparticles do not have a clear crystalline structure [ 44 ]. The XRD peaks with diffraction angle of 2θ are 31.3°, 36.93°, 55.7°, 59.3°, 65.3° are related to the planes of (220), (311), (422), (511), (440) respectively (JCPDS: 42-1467) [ 45 ].…”
Section: Resultsmentioning
confidence: 99%